Pengaruh profitabilitas, ukuran perusahaan dan pertumbuhan perusahaan dalam memprediksi kondisi financial distress - Indria Sri Astria; Nor Norisanti; Faizal Mulia Z (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
This study aims to analyze the influence of profitability, company size and company growth in predicting financial distress in the property and real estate sub-sectors. The data was selected using a purposive sampling method and there were 10 companies listed on the Indonesia Stock Exchange from 2020-2022 which were the research samples. This study uses the normality test, the coefficient of determination, the multiple correlation test, the f test and the T test. To analyze the data, the results indicate that the company's profitability and growth have an influence on financial distress. Meanwhile, Company Size has no effect on Financial Distress.